The Fatigue Behavior of Restorations Used Under the Rest of Removable Partial Denture - Farzin M; Bahrani F; Nejabat N; Meshki R (Shiraz University of Medical Sciences, 2014)
Statement of Problem: The question about resistance of resin composites under rest in removable partial denture (RPD) is still unanswered. It is important to find the strongest material that withstands the applied stresses when used under RPD components. Objectives: To evaluate and compare the fatigue behavior of amalgam and composite restorations used under the rest of the removable partial denture. Materials and Methods: Forty-five permanent human upper premolars were prepared with standard class II DO cavities and divided into 3 groups of specimens (n=15 for each group). Group I was filled with amalgam (Dispersalloy), group II and III were filled with resin composite (Flitek Z250 and Tetric ceram, respectively). The teeth were stored in distilled water for 14 days before testing. After thermocycling, the "staircase" approach was used to determine the flexural fatigue limits (FFL). The mean differences were evaluated using One-Way ANOVA and post hoc test. Results: A strong significant differences of flexural fatigue strength have been found between amalgam and composite groups (P<0.001). There was no significant difference between two groups of resin composite (P=0.1). Conclusions: To achieve more flexural fatigue strength in the rest seats, the use of resin composite in comparison with amalgam is recommended.